Análise do curso preparatório para agentes de segurança penitenciária femininas e sua relação com a formação em direitos humanos - Sarmento, Virginia Alves (2014)
The objective of this research was to analyse the preparatory course for Female Prison Officers, held in the state of Paraiba between 2008 and 2013 and its relation with training in human rights. The methodology employed included bibliographic research in books, scientific articles, theses and dissertations which dealt with the issue; documentary research in the School of Prison Management; and interviews with ten prison officers who work at the Maria Julia Maranhão Centre of Female Re-education (CRFMJM). Data collection was carried out between October 2013 and February 2014. The interviews were recorded and the data organised and analysed making use of Bardin‟s (2002) technique for the analysis of content. The dissertation is organized in fourth chapters: the first deals with questions about the prison as a social system and the work of the prison staff; the second discusses the education and training of prison staff considering the guide-lines offered by specific legal documents; the third discusses the issue of education in human rights in the process of prison officer training; and the fourth is dedicated to reflections on the data collected. Our systematisation of the discussion on the data allowed us to conclude, in general terms, that the course informed more than formed the officers concerning their functions in the prison and did not take the training of officers based on the principles of human rights as its chief goal. For this reason, we propose the use of a methodology founded on education in human rights for the training of prison staff.